Analysis Of Form And Presentation On The Song “Bingung” By Iksan Skuter - Putra, Lingga Nusantara; Wafa, Mochammad Usman (Jurnal Seni Musik, 2021)
Iksan Skuter is a musician who likes to voice songs with the theme of social criticism. In this paper, the writer focuses on one song by Iksan Skuter, namely the song titled Bingung. The song Bingung contains a social critique of contradictions that have always been a concern of the people in Indonesia. The reason why the writer made the song Bingung by Iksan Skuter the focus of the research is that according to the writer this song has simplicity in the form of music, has a series of melodies that are easy to remember, has straightforward lyrics, and this song is quite in demand by the public, this can be seen from the following: the number of individuals and groups who re-sung this song. The research method used was descriptive qualitative with a content analysis approach. Data collection techniques include: observation, interview, and documentation techniques. The results showed that the song Bingung consisted of three parts, namely part A, part B, and part C with sentence structures or musical phrases part A (a, x), B (b, b1) and C (c, z).